Microzonation of Cisarua District using Horizontal Vertical Spectral Ratio - Erlangga Ibrahim Fattah (JIIF (Jurnal Ilmu dan Inovasi Fisika), 2021)
The Bandung region is part of the framework of the Indonesian tectonic system, namely the tectonic plate meeting zone, where the Indo Autralia plate is infiltrated under the Eurasian plate in a convergent manner. The subduction process produces an effect in the form of an active fault geological structure in the Bandung area. One of these active faults is the Lembang Fault, which has a length of ± 29 kilometers and a shear acceleration of 3 to 5.5 millimeters per year. The microtremor measurement method is a passive geophysical method that utilizes natural subsurface vibrations so that it can provide dominant frequency data and amplification factors for soil layers. Based on the results of seismic susceptibility research using microtremor measurements using the HVSR method in the Lembang Fault zone in Cisarua Sub-District, it can be seen that the distribution of the dominant frequency values tends to be influenced by lithology and topography. In the research area, it is known to have a dominant frequency value that varies due to the different types of lithological units. In general, the dominant frequency ranges from 1-3 Hz because it is dominated by tuff sand and tuff pumice, and areas composed of volcanic breccias have a dominant frequency value between 3-6 Hz. Meanwhile, the amplification factor value will be influenced by rock deformation and weathering. The area that has a very high amplification factor value is in the southeast of the study area with an A0 value greater than 5. This indicates that the area is composed of a layer of thick and not dense tuff sand.